Reversibility of Assets of Concessionaires of Local Fixed Telephony considering the Theory of Responsive Regulation - Pinheiro, Alexandre Pereira (Law, State and Telecommunications Review, 2019)
Purpose ”“ The purpose of this article is to investigate whether the reversal to the public domain of assets owned by the current service provider, in the context of concession of public telecommunications service, is still the only, or even better, way to achieve the objectives it aims, especially the continuity of the service, in relation to the theoretical framework of Ayres and Braithwaite’s Theory of Responsive Regulation. Methodology/approach/design ”“ The research will consider the structuring statutes of the telecommunications sector, the secondary norms produced by Anatel, as well as national and foreign literature on the subject. Findings ”“ After analyzing the doctrinal and normative framework on the subject of reversible assets in the telecommunications sector in light of the Responsive Theory of Regulation, it is believed that it will be possible to discern solutions that best fit the analyzed Theory, and there are many arguments against the preservation of the current model, which does not incorporate adequate regulatory modeling to address the issue.